PELATIHAN PENCATATAN KEUANGAN DENGAN BERBASIS ELEKTRONIC CASH REGISTER PADA ERLENE HANDYCRAFT - Dewi Kartikasari; Maria Rosa Kumala Dewi; Titik Dwiyani (LPPM Universitas Nusa Mandiri, 2026)
This community service initiative aims to enhance the digital capabilities and competitiveness of Erlene Handycraft, an SME in Sukoharjo operating in the handicraft sector, through training on Electronic Cash Registers (ECR). The Participatory Action Research (PAR) method was used to ensure the active involvement of partners throughout the entire community service process. The implementation process began with an outreach campaign aimed at introducing the program’s objectives, explaining the benefits of using electronic cash registers, and agreeing on the partners roles in the implementation process. The second phase, training on the cash register system focused on how to speed up transaction processes and accurately record sales. In the third phase, the previously designed ECR system was put into use. The fourth phase, mentoring and evaluation was conducted immediately following the training to ensure the effectiveness of the provided solution. In the final phase, focused on program sustainability, a set of ECR devices was handed over to partners to support business development and record sales transactions. The results of the activity showed a significant positive impact. MSME owners gained a better understanding of the importance of the cash register system in avoiding errors in receipt issuance, which was clearly evident from a comparison of conditions before and after implementation. Financial record keeping became easier and more organized. Understanding of financial record keeping improved, including the ability to calculate inventory inflows and outflows more efficiently. The program’s success was reflected in a 5% increase in revenue.